Mothering across cultures : postcolonial representations - Reyes, Angelita Dianne (University of Minnesota Press, 2002)
Blending the personal and the historical, the practical and the theoretical, Angelita Reyes draws on a wide range of texts from Africa and the African diaspora to establish mothering as a paradigm of progressive feminisms. Reyes creates a comparative dialogue among the fictions of five postcolonial women writers: Toni Morrison, Paule Marshall, Simone Schwarz-Bart, Jean Rhys, and Mariama Bâ.